EFEKTIVITAS VIDEO ANIMASI SETTING INKUIRI UNTUK MENINGKATKAN KETERAMPILAN PROSES SAINS SISWA SEKOLAH DASAR - Nurhayati Nurhayati; Dimas Qondias (JURNAL PENDIDIKAN DASAR PERKHASA: Jurnal Penelitian Pendidikan Dasar, 2023)
This research aims to analyze the effectiveness of inquiry setting animated videos to improve elementary school students' science process skills. This type of research is a quasi-experiment carried out at elementary schools in Pringgabaya sub-district, East Lombok. The data collection method for science process skills is obtained through observations made by students which are developed through LKPD. The data analysis technique was carried out using inferential statistical analysis using the Anava test. This research obtained results that animated videos of inquiry settings were more effective in improving science process skills compared to conventional learning. This is reinforced by the ES value of 4.131 in the high effectiveness category. These results recommend that animated videos with inquiry settings are good to apply to improve the science process skills of elementary school students in Pringgabaya District, East Lombok.